2009
DOI: 10.1049/iet-com.2008.0068
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the capture and dissemination of measurements from high-speed networks

Abstract: The production of a large-scale monitoring system for a high-speed network leads to a number of challenges. These challenges are not purely techinical but also socio-political and legal. The number of stakeholders in a such a monitoring activity is large including the network operators, the users, the equipment manufacturers and of course the monitoring researchers. The MASTS project (Measurement at All Scales in Time and Space) was created to instrument the high-speed JANET Lightpath network, and has been ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…NFDUMP mengumpulkan dan mengolah data dari NetFlow dengan menggunakan perintah dari command line. [12]. Untuk kepentingan ini maka digunakan sebuah tools yang disebut NFDUMP.…”
Section: Pendahuluanunclassified
“…NFDUMP mengumpulkan dan mengolah data dari NetFlow dengan menggunakan perintah dari command line. [12]. Untuk kepentingan ini maka digunakan sebuah tools yang disebut NFDUMP.…”
Section: Pendahuluanunclassified
“…Pilli proposed a method that collects packets under the TCP/IP protocol to analyze the common characteristics of attacks so as to filter suspicious packets [9]. However, high data rate of network traffic creates difficulties for network forensics in the capture and preservation of all network packets [10]. Kaushik, through scanning ports, found that attackers could find potential loopholes and then use these vulnerabilities to attack hosts [11].…”
Section: Related Workmentioning
confidence: 99%
“…Article from Clegg et al [5] published in 2008 comprehensively describes practical and legal aspects of monitoring of a 10 G research network. Authors also provide several data sets containing captured packet headers as a part of their contribution.…”
Section: Related Workmentioning
confidence: 99%